Evaluating User Experience and User Engagement of the AstraPay Mobile Wallet Using UEQ+ and UES - Kelvin Isaiah Sitorus; Afen Prana Utama Sembiring; Yuni Marlina Saragih (Ali Institute of Research and Publication, 2026)
This study was conducted to see the extent of user experience (User Experience) and user engagement (User Engagement) on the AstraPay digital wallet application, considering that these two things are important keys that determine the success and sustainability of a digital application in the eyes of its users, where user experience is measured using the User Experience Questionnaire Plus (UEQ+) and user engagement is measured through the User Engagement Scale (UES), through a quantitative approach by distributing online questionnaires to 405 AstraPay users in Indonesia whose data is then analyzed using validity and reliability tests, calculating the average for each scale, Spearman correlation tests, to simple linear regression. The results, all UEQ+ scales show positive evaluations with Usefulness and Clarity recording the highest scores, while in the UES the Aesthetic Elements and Reward Factor scales performed very well, while Perceived Usability is the aspect with the lowest score. Regression analysis shows a determination coefficient value of R² = 0.251 with a regression coefficient B = 0.275 (p < 0.001), so that user experience has a positive and significant effect on user engagement, which means that the better the quality of experience perceived by users, the higher their level of engagement with the AstraPay application